Association between TIMP-2 gene polymorphism and breast cancer in Han Chinese women - Wang, Kai; Wang, Guanying; Huang, Shangke; Luo, Anqi; Jing, Xin; Li, Gang; Zhou, Yi; Zhao, Xinhan (BMC cancer, 2019)
TIMP-2 gene plays an important role in the development of breast cancer. The present study was conducted to evaluate whether TIMP-2 gene polymorphisms are associated with breast cancer risk in a Han Chinese cohort. Six single nucleotide polymorphisms (SNPs) within the TIMP-2 gene in 571 breast cancer and 578 healthy control subjects were genotyped through the Agena MassARRAY. Logistic regression analysis was used to assess the influence of TIMP-2 polymorphisms on breast cancer. Functional annotation of TIMP-2 variants and TIMP-2 expression were analyzed by bioinformatics. Bioinformatics analysis found that rs4789936 was likely to affect transcription factor binding, motifs, DNase footprint, and DNase peaks; and TIMP-2 was under-expressed in breast cancer, the risk allele of rs4789936 was associated with increased expression of TIMP-2 in peripheral blood samples. Importantly, individuals carrying TIMP-2 rs2277698 T allele have a 19% lower risk of breast cancer than individuals with allele C, providing protection (OR = 0.81, 95%CI = 0.67-0.99, p = 0.041). In the breast cancer patients with c-erb positive and PR positive, when the CC genotype was used as a reference, individuals carrying the TT genotype increased the risk of breast cancer. Haplotype analysis showed "TCC" was associated with a reduced risk of breast cancer (OR = 0.79, 95%CI = 0.63-0.97, p = 0.028). Our study indicated that TIMP-2 rs2277698 was associated with breast cancer susceptibility.